Idealized simulations with Antarctic meltwater - Ji-Hoon Oh (10272338); Kyung Min Noh (8522061); Hyung-Gyu Lim (10272343); Emilia Kyung Jin (10272346); Sang-Yoon Jun (10272348); Jong-Seong Kug (8522554) (2021)
Idealized simulations result, which is used for the present research, was attached as netCDF files. Idealized ensemble experiments with the Geophysical Fluid Dynamics Laboratory (GFDL) model CM2.1 coupled with the biogeochemical (BGC) model Tracers of Phytoplankton with Allometric Zooplankton version 2 (TOPAZv2) (https://www.gfdl.noaa.gov/earth-system-model/, Dunne et al., 2013). The version of GFDL-CM2.1-TOPAZ used here is the same as that used in Lim et al. (2018, 2019), in which detailed descriptions of the model configuration and initial conditions are given. Three different simulations were conducted. The first was a long-term control simulation over 2000 years (CTRL) applying a fixed carbon dioxide (CO2) concentration in 1990 of 353 parts per million (ppm). The CTRL experiment in the present study was analyzed only for the last 1000 years to avoid long-term drift. The other two experiments were global warming simulations that either included additional Antarctic meltwater forcing (GWMW) or excluded it (GW). These simulations were performed over 100 years with eight ensembles. The individual ensembles had different initial conditions taken from CTRL every 100 years. Both global warming simulations were prescribed by increasing atmospheric CO2 concentration at a rate of 1% year−1 until it doubled (706 ppm) from years 1 to 70 in the model, and then the CO2 concentration (706 ppm) was fixed until the end of the model integration.